Millimeter-Wave Fully Integrated Dielectric Resonator Antenna and Its Multi-Beam Application - Ma, Chaojun; Zheng, Shao Yong; Pan, Yong Mei; Chen, Zhe (IEEE transactions on antennas and propagation, 2022)
To address the issues of the inconvenient fabrication and integration for millimeter-wave (MMW) dielectric resonator antennas (DRAs), a new configuration is proposed. First, a dielectric resonator with artificial electromagnetic boundaries is implemented by introducing the electromagnetic band-gap structure along the four side-wall boundaries of a certain dielectric region on a printed circuit board. The electromagnetic bandgap (EBG) structure is constructed using a printed array of periodic upside-down mushroom-type unit cells. The resonant-mode analysis reveals that the proposed DR can support conventional dielectric resonator modes and dense dielectric patch (DDP) cavity modes simultaneously. To excite the DR, a substrate-integrated gap waveguide transmission line is embedded in the proposed structure for implementing a fully integrated DRA. For demonstration, a fully integrated dielectric resonator antenna (FIDRA) operating at 31 GHz is designed. Simulated results show that the antenna offers an 11.5% −10 dB impedance bandwidth (29.6 to 33.2 GHz), in which a peak gain of 7.85 dBi is obtained. As an extension, a multi-beam antenna array composed of a 1 × 4 FIDRA antenna array and a SIGW 4 × 4 Butler matrix is designed and fabricated. The experimental results verified the effectiveness of the proposed configuration in integrating the DRA and feeding network.